Duplication of the Xq27.3–q28 region, including the FMR1 gene, in an X‐linked hypogonadism, gynecomastia, intellectual disability, short stature, and obesity syndrome. Issue 9 (29th July 2013) - Hickey, Scott E.; Walters‐Sen, Lauren; Mosher, Theresa Mihalic; Pfau, Ruthann B.; Pyatt, Robert; Snyder, Pamela J.; Sotos, Juan F.; Prior, Thomas W.
Abstract: In 1979 a "new" syndrome characterized by X‐linked inheritance, hypogonadism, gynecomastia, intellectual disability, obesity, and short stature was described. The now‐36‐year‐old propositus was recently referred to the genetics clinic for profound intellectual disability. Fragile X testing initially demonstrated a duplication of the FMR1 region, and upon further testing we identified an Xq27.3–q28 8.05 Mb‐long duplication responsible for a syndrome. Our report describes the molecular and clinical aspects of the X‐linked syndrome. Our results suggest that male patients with intellectual disability, hypogonadism, short stature, and gynecomastia should be further investigated for rearrangements in the Xq27.3–q28 region. In the future, when more cases of the duplication are identified, it may become possible to more accurately determine the specific genes affected by overexpression and responsible for the phenotype. © 2013 Wiley Periodicals, Inc.